SUPERVISION OF FIBER OPTIC NETWORK INFRASTRUCTURE MANAGEMENT BY THE DEPARTMENT OF PUBLIC WORKS IN THE CITY OF MEDAN - Manahan Favian; Tunggul Sihombing (Yayasan Wayan Marwan Pulungan, 2023)
The increasing number of internet users in Indonesia has resulted in an increased need for internet infrastructure. The city of Medan is one of those affected, where there are many chaotic internet infrastructures. The Medan City Public Works Service has overcome this phenomenon, but many violations are still found in the field. The purpose of this study was to determine the supervision of licensing management for fiber optic network infrastructure by the Public Works Department of Medan City. The research method used is a qualitative research method with an approach. The results of research in the field show that the supervision of licensing management carried out by the Medan City Public Works Service has not gone well. This can be observed from the many installations of internet network infrastructure in Medan City that are not in accordance with Medan Mayor Regulation Number 17 of 2020 concerning Guidelines for Structuring and Controlling Telecommunication Towers and Fiber Optic Networks. Among them are installations that do not get permission from the local community, disruption of access to and out of 4-wheeled vehicles, and construction toe points that are too close to the side of the sidewalk.